Primerjalnopravni pregled nepravdnih postopkov v družinskih zadevah v razvojni perspektivi - Rijavec, Vesna (Podjetje in delo, 2018)
Due to the need to harmonise procedural rules of non-contentious proceedings with the new conceptual solutions of the Family Code in the area of family relationships, the adoption of the new Act on Non-Contentious Civil Proceeding is necessary. The analysis of comparative legal examples shows that family matters need to be tackled as fully and uniformly as possible, which the non-contentious rules with more flexible and less formal nature certainly enable. The article discusses the necessary procedural adjustments of the fundamental principles and general provisions of the non-contentious procedure. Arguments are based on an overview of the German and Austrian rules, which are most comparable to the Slovenian system because family matters are decided in a non-contentious proceeding in both jurisdictions. The authors further discusses the regulation of non-litigious proceedings in Italy and France, which fall into the group of regulations that provide the basis for regulating non-contentious matters in civil procedural codes.
Keywords: družinska zadeva; nepravdni postopek; pojem nepravdnega postopka; pravdni postopek; primerjalnopravni sistem nepravdnih postopkov; razmejitev; temeljna načela